Turismo Accesible para el servicio de alojamiento del cantón Caluma provincia de Bolívar, en el año 2024. - Tapia Tapia, Lady Marilu (2025)
This research focused on the development of a manual of good accessibility practices for tourist accommodation services in the Caluma canton, Bolívar province, based on the problem related to the lack of accessibility in these establishments. To achieve this objective, a mixed approach was adopted, which combines the qualitative with the quantitative, with a research design based on the analysis of documents, complemented by the application of interviews and a bibliographical record on the accommodation service in the canton. First, an exhaustive bibliographic review of scientific articles, theses and research projects was carried out. Subsequently, a field trip was carried out, during which an observation form was filled out to evaluate the accessibility of the establishments. In addition, interviews were conducted with the owners of the accommodations to find out their level of knowledge about the accessibility of their facilities. Finally, with the results obtained, it was concluded that, although the Caluma canton has beautiful landscapes and a pleasant climate, it is still necessary to implement improvements in the accessibility of the accommodation establishments existing in the area.